2008
DOI: 10.1093/chemse/bjn071
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Peripheral Receptor Code and Perceived Odor Quality

Abstract: The discrimination of thousands of odorants is mediated by several hundred olfactory receptors (ORs). It is generally accepted that the main strategy in encoding odor quality is a combinatorial receptor code scheme, in which odorants are discriminated by different sets of ORs. In the present study, we classified 12 test odorants by their receptor codes and perceived odor qualities to examine whether odorants showing similar receptor codes are also similar in their odor qualities. Similarities of receptor codes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
0
28
1
Order By: Relevance
“…Several studies have attempted to connect odorant physicochemical properties to the olfactory perception; however, odor coding remains largely unknown [4][9]. To recognize odorant molecules, the olfactory system uses combinatorial coding scheme to encode odor identities by different combinations of ORs [10], [11]. Indeed, it has been shown that one odorant can interact with several different ORs and one OR can be activated by a number of molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have attempted to connect odorant physicochemical properties to the olfactory perception; however, odor coding remains largely unknown [4][9]. To recognize odorant molecules, the olfactory system uses combinatorial coding scheme to encode odor identities by different combinations of ORs [10], [11]. Indeed, it has been shown that one odorant can interact with several different ORs and one OR can be activated by a number of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, only a small number of experimental studies have identified odorant-OR interactions in various organisms, mainly in mammals and insects [13][19]. Despite some efforts to elucidate the link between activation of ORs and odor perception, our understanding of peripheral olfactory coding in mammals remains limited [11], [20][24].…”
Section: Introductionmentioning
confidence: 99%
“…Human ability to recognize a wide variety of odorants is the result of the high number of olfactory receptors1011 encoded by 339 intact genes12. The process of detecting odors starts with olfactory receptors, located in the cilia of the olfactory sensory neurons13.…”
mentioning
confidence: 99%
“…Some phenylpropanoids, including safrole, have low affinity for the olfactory receptor to which eugenol binds. 9) Furthermore, Furudono et al 10) reported that eugenol and vanillin 7) stimulated a different type of olfactory receptor from the receptors that have high affinities with trans-cinnamaldehyde, trans-anethole, and estragole. These results suggest that the appetite-enhancing effects of inhaling curry powder essential oil may be caused by stimulation of several receptors.…”
Section: Discussionmentioning
confidence: 99%